Reconstructing the holocene. Benthic foraminifera as a proxy for the paleoceonography of the nordic seas - Baker, May Lizabeth (UiT Norges arktiske universitet, 2017)
The benthic foraminifera of two marine sediment cores were studied as a proxy for paleoenvironment reconstructions throughout the Late to Early Holocene. The two cores were sampled in different localities to allow a spatial comparison of changing environments in the Nordic Seas and sampled for benthic foraminiferal assemblages, grain size, IRD, sortable silts and benthic foraminifera isotopes. While attempts at correlation were made, differing sedimentation rates made this difficult. A cold period spanning ~1000 years can be seen in both sediment records, attributed to the Dark Ages Cold Period. Benthic assemblages and isotope records show only vague similarities throughout the Late Holocene, suggesting that the core environments were subject to differing climatic influences due to their different localities, with only large scale climatic events effecting both areas equally